Manajemen Strategis pada Sektor Publik di Provinsi Sulawesi Tenggara - Satyadharma, Maudhy; Suhri Kasim, Syaifudin; Ode Fasikin, La; Ode Abdul Harlan, La (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2025)
This study attempts to examine the implementation of strategic management in the public sector in Southeast Sulawesi Province, especially in the scope of the Office of the Governor's Expert Staff for Government, Law, and Politics of Southeast Sulawesi Province. This study uses a qualitative research approach using a descriptive method. The purpose of descriptive research is to describe problem solving in accordance with existing facts systematically and accurately. The results of the study found that the implementation of strategic management is closely related to the current state of ASN. Good strategic management can provide clear direction, improve competence, and motivate ASN to work more effectively. However, challenges in strategic management, such as rigid bureaucracy and resistance to change, also reflect various issues faced by ASN. To optimize ASN performance, it is necessary to implement strategic management, as well as adequate support in dealing with change and this has been done slowly but surely in the scope of the Office of the Governor's Expert Staff for Government, law and politics of Southeast Sulawesi Province.